Pengaruh Komunikasi, Kepuasan Kerja, dan Kepemimpinan Terhadap Komitmen Organisasi dan Kinerja Tenaga Kependidikan STIE ADI UNGGUl BHIRAWA (STIE âAUBâ) Surakarta - Pahlawi, Lukman Ahmad Imron; Utomo, Agus (Sumatera Research, 2017)
This study aims to analyze the influence of communication, job satisfaction and leadership towards organizational commitment and performance of education staff STIE